Formative assessment in distance learning: narratives of Indonesian senior secondary school EFL teachers - Yulianita Listya Dewi; Mutammam (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
Assessment is a pivotal endeavor where the teacher can provide feedback, evaluation and solutions on students’ learning so that the teacher can find out the level of students’ understanding of the lesson that has been taught and see the abilities and difficulties faced by the students to determine what students need. Based on the current situation, the COVID-19 pandemic has led to changes in the learning system from offline learning to distance learning with online mode. In response to this, teachers and students need to adapt to the online mode of teaching and learning process. To fill this gap, the current study aims to explore the way of English teachers in conducting formative assessments related to students’ proficiency during distance learning. Designed in narrative research, data are garnered through semi-structured interviews with three Indonesian English teachers of senior secondary school. The interview seeks to explore the methods or strategies of English teachers towards online formative assessment during distance learning. The results of this study indicate that formative assessment during distance learning is carried out online with one or more combinations of language skills.